Comparison of interferon gamma release assay and CXCL9 gene expression assay for the detection of Mycobacterium bovis infection in African lions (Panthera leo) - Gumbo, Rachiel; Sylvester, Tashnica T.; Parsons, Sven D. C.; Buss, Peter E.; Warren, Robin M.; van Helden, Paul D.; Miller, Michele A.; Kerr, Tanya J. (Frontiers in Cellular and Infection Microbiology, 2022)
Mycobacterium bovis (M. bovis) infection has been identified in both domestic and wild animals and may threaten the conservation of vulnerable species including African lions (Panthera leo). There is a need to develop accurate ante-mortem tools for detection of M. bovis infection in African big cat populations for wildlife management and disease surveillance. The aim of this study was to compare the performances of two immunological assays, the QuantiFERON®-TB Gold Plus (QFT) Mabtech Cat interferon gamma release assay (IGRA) and QFT CXCL9 gene expression assay (GEA), which have both shown diagnostic potential for M. bovis detection in African lions. Lion whole blood (n=47), stimulated using the QFT platform, was used for measuring antigen-specific CXCL9 expression and IFN-γ production and to assign M. bovis infection status. A subset (n=12) of mycobacterial culture-confirmed M. bovis infected and uninfected African lions was used to compare the agreement between the immunological diagnostic assays. There was no statistical difference between the proportions of test positive African lions tested by the QFT Mabtech Cat IGRA compared to the QFT CXCL9 GEA. There was also a moderate association between immunological diagnostic assays when numerical results were compared. The majority of lions had the same diagnostic outcome using the paired assays. Although the QFT Mabtech Cat IGRA provides a more standardized, commercially available, and cost-effective test compared to QFT CXCL9 GEA, using both assays to categorize M. bovis infection status in lions will increase confidence in results.